Effect of Sand Pretreatment on Bio-Stabilization Using Rhizopus oligosporus - Zhafirah, Athaya; Fauziah, Fitria Nurhaliza; Febrijanto, Rudy; Yogaswara, Dendi (Journal of Geoscience, Engineering, Environment, and Technology, 2026)
Ottawa sand is a type of sand widely used in geotechnical research for its uniformity and high silica content. However, Ottawa sand is classified as a non-cohesive soil, lacking intergranular bonds, resulting in low shear strength. Therefore, a soil improvement method that enhances the material's mechanical stability is needed. This study aims to analyze the effect of Ottawa sand pretreatment on increasing soil shear strength through a bio-stabilization method using the fungus Rhizopus oligosporus. The research method used is a laboratory experimental method with an unconfined compression test. Ottawa sand samples were divided into three treatments: normal treatment (S-0), washed sand treatment (S-1), and washed and oven-dried treatment (S-2). Each sample was mixed with tempeh yeast containing Rhizopus oligosporus and distilled water, each at 5% of the sand weight. The curing process was conducted in a closed container, with temperature, humidity, and mycelium development monitored during incubation. The results showed that sand pretreatment increased the soil's unconfined compressive strength. The samples treated with washing and oven drying (S-2) had the highest unconfined compressive strength of 9.72 kPa and shear strength of 4.86 kPa at 12 days of curing. Meanwhile, the samples without pretreatment showed lower unconfined compressive strengths. Visually observed mycelial growth showed a more even distribution in the samples with sand pretreatment. The results of this study indicate that bio-stabilization using Rhizopus oligosporus has the potential to be a more environmentally friendly soil-improvement method for increasing the stability of sandy soil.